Formulation and Evaluation of Rosuvastatin Fast Dissolving Tablets - Ramu, A.; Vidyadhara, S.; Devanna, N.; Anusha, Ch.; Keerthi, J. (Asian Journal of Chemistry, 2013)
Rosuvastatin calcium (RST) is a selective and competitive inhibitor of HMG-CoA reductase, mainly used in the treatment of hypercholesterolemia, hyper triglyceridemia and atherosclerosis. In this work a new attempt was made to enhance the solubility, dissolution rate and oral bioavailability of poorly soluble rosuvastatin by formulating it as solid dispersions using various techniques with polyethylene glycol (PEG) 6000 as a carrier. Fast dissolving tablets of rosuvastatin were prepared with super disintegrants like sodium starch glycolate, croscarmellose sodium, pregelatinized starch and mannitol from the optimized solid dispersions. Tablets were evaluated for physical parameters and drug release by in vitro dissolution studies. Surface characteristics, drug-excipient interactions and crystal morphology of optimized solid dispersions were evaluated by SEM analysis, DSC and XRD studies, respectively.